Process Management 2010
DOI: 10.5772/8456
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines to Improve Construction and Demolition Waste Management in Portugal

Abstract: The content of the book has been structured into four technical research sections with total of 18 chapters written by well recognized researchers worldwide. These sections are: 1. process and performance management and their measurement methods, 2. management of manufacturing processes with the aim to be quickly adaptable after real situation demands and their control, 3. quality management information and communication systems, their integration and risk management, 4. management processes of healthcare and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 3 publications
(3 reference statements)
0
2
0
1
Order By: Relevance
“…Srour, Chong and Zhang (2012) have shown that in most of these instances it is the designer who has the greatest control over possible changes that can improve future reuse and recycling. Couto and Couto (2010) have also shown that the designer has the greatest potential impact on the future levels of material and component reuse. The major factor preventing the higher order reuse of materials and components is that they have not been designed with future recovery in mind.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Srour, Chong and Zhang (2012) have shown that in most of these instances it is the designer who has the greatest control over possible changes that can improve future reuse and recycling. Couto and Couto (2010) have also shown that the designer has the greatest potential impact on the future levels of material and component reuse. The major factor preventing the higher order reuse of materials and components is that they have not been designed with future recovery in mind.…”
Section: Discussionmentioning
confidence: 99%
“…Durmisevic and Brouwer (2002) have research the specifics of designing buildings for Published by ECSDEV, Via dei Fiori, 34, 00172, Rome, Italy http://ecsdev.org future material recovery and they propose four levels in a hierarchy of end of life cycle scenarios; reuse and remanufacture, recycling, incineration, and landfill. More recently research in Portugal (Couto & Couto, 2010) has proposed a waste management hierarchy for construction and demolition waste based on the minimisation of resource consumption and environmental damage; these included six levels of reduce, reuse, recycle, compost, incinerate, and landfill.…”
Section: Recycling Hierarchymentioning
confidence: 99%
“…When managed properly, construction waste is minimised in landfills, preserving valuable landfill space, and recycled construction waste is transformed into a high-value secondary raw material that can serve other construction purposes. 43,44 For instance, the replacement of coarse natural aggregates with coarse recycled aggregates from C&D waste in the production of concrete is one such practice that reduces the consumption of natural mineral resources, and provides an opportunity for recycling construction and demolition waste into raw material. Nevertheless, industry representatives in most countries are hesitant to use recycled aggregates in concrete.…”
Section: Construction Waste Managementmentioning
confidence: 99%
“…Nesse cenário, o reaproveitamento dos elementos de construção torna-se uma preocupação crucial para evitar a exaustão dos recursos naturais (AMÔEDA, 2009;COUTO, 2010). Segundo Diyamandoglu e Fortuna (2015), a recuperação de materiais e componentes com potencial vitalício evita a extração de materiais virgens, evita a liberação associada de gases de efeito estufa, economiza energia, consumo de água e evita custos de descarte de resíduos sólidos.…”
Section: Introductionunclassified